2013
DOI: 10.1177/1355819613479945
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and carers' views on communication and information provision when undergoing assessments in memory services

Abstract: Communication and information need improvement for patients undergoing assessment for possible dementia, especially for those considered unlikely to benefit from medication and those with mild cognitive impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(69 citation statements)
references
References 23 publications
3
66
0
Order By: Relevance
“…Caregivers experienced a lack of appropriate information and professional advice on how to get support and how to care for their relatives. As Abley et al () highlighted in their study, the General Practitioners (GP) and memory clinics have key roles in the process of diagnosis, informing about the condition and treatment and educating the patient and their families via communication and sharing informative leaflets about local services. The current situation in Estonia would benefit from increasing the role of the GP in the assessment and early diagnosis of dementia, and also in the process of information and communication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers experienced a lack of appropriate information and professional advice on how to get support and how to care for their relatives. As Abley et al () highlighted in their study, the General Practitioners (GP) and memory clinics have key roles in the process of diagnosis, informing about the condition and treatment and educating the patient and their families via communication and sharing informative leaflets about local services. The current situation in Estonia would benefit from increasing the role of the GP in the assessment and early diagnosis of dementia, and also in the process of information and communication.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the caregivers had been providing assistance for several years and resulting in a high burden of care (Akpınar, Küçükgüçlü, & Yener, ; Erol et al, ). Their workload was affected by the caregiver's (in)experience with dementia as a specific condition, a lack of information and poor support (Abley et al, ; Karlsson et al, ; Lethin et al, ; Parker, Mills, & Abbey, ; Teel & Carson, ). The demands of a caregiver's role also influenced family relationships, employment, financial resources, social activities, well‐being and health (Gallicchio, Siddiqi, Langenberg, & Baumgarten, ; Stensletten, Bruvk, Espehaug, & Drageset, ; Tang, Ryburn, Doyle, & Wells, ; Verbeek et al, ; Verbeek‐Oudijk et al, ; Zabalegui et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] The aims of this study were: to describe the change in health related quality of life (HRQL) over the first 6 months after first referral to MAS; to assess whether patient characteristics, including diagnosis, are associated with changes in HRQL; and to determine if use of antidementia drugs and non-pharmacological post-diagnostic therapies are associated with improved HRQL among those patients diagnosed with dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Patients and carers attending excellent services were more likely to have received written information on certain specific topics (but not others) and were more likely to have had opportunity to provide feedback on the service. However, there was no difference between whether patients and carers felt they had enough information in accredited or excellent clinics, suggesting that they may not be aware of what they are entitled to receive, in line with previous research highlighting limited provision of written information within memory clinics (van Hout et al , ; Foreman et al , ; Abley et al , ; Hodge et al, ). Ideally, information should be tailored to individual need (Manthorpe et al , ) so as to avoid patients and carers being subjected to information overload.…”
Section: Discussionmentioning
confidence: 97%
“…Obtaining feedback from patients and carers is considered vital in making improvements to health services (van Hout et al , ; Royal College of Psychiatrists, ). Previous evaluations of patient and carer experiences of memory clinics have suggested that while on the whole they were very satisfied with the service and treatment received there was room for improvement with regard to the provision of information (van Hout et al , ; Foreman et al , ; Abley et al , ; Hodge et al , ).…”
Section: Introductionmentioning
confidence: 99%